COMPARISON OF ABSORBED DOSE FOR HIGH ENERGY PHOTON BEAMS DETERMINATION BY IAEA TRS 398 AND IAEA TRS 277 FOR 8 HOSPITALS IN BANGKOK - ISRANGKUL NA AYUTHAYA, Isra; SURIYAPEE, Sivalee; JUMPANGERN, Chotika; SANGHANGTHUM, Taweap; OONSIRI, Sornjarod (The ASEAN Journal of Radiology, 2023)
Absorbed dose to water is of great important in radiation therapy. The IAEA TRS 277 protocol using an ionization chamber calibrated in air in term of air kerma has been used for absorbed doses determination in all therapy centers in Thailand. In recent year, a new code of practice IAEA TRS 398 based on chamber calibration in term of absorbed doses to water was introduced to reduce uncertainties arising from calculation of absorbed dose to water using air kerma calibration factor. To implement this new protocol into a clinic, a comparison of the two protocols should be studied. The study was undertaken for 8 hospitals in Bangkok with 6, 10 and 18 MV x-ray beams from linear accelerators and gamma beams from Co-60 machines. The measurements were made in a water phantom at the reference depth as specified in the protocols with two types of dosemeter system, one was the control dosemeter and the other was the hospital dosemeters. The results showed that the absorbed dose determined by TRS 398 and TRS 277 were agreeable within 1% for all energies of photon beams in 8 hospitals. The result is consistent with other studies. The hospital dosemeters showed a maximum discrepancy of 0.7%, 0.7%, 0.5% and 0.5% for 6, 10 and 18 MV x-ray beams and Co-60 beams, respectively, The absorbed doses measured from the control dosemeter were comparable to the hospital dosemeters within 1.8%. Agreement between control dosemeter and hospital dosemeter with TRS 398 is slightly better than the agreement with TRS 277. A transition from TRS 277 to TRS 398 would not significantly change the absorbed dose values of high energy photon beams. The new protocol could be implemented to all of the hospitals in this project with confidence.